2021
DOI: 10.3390/cryst11091011
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling of Methane: Perspective for High-Value C2 Chemicals

Abstract: The oxidative coupling of methane (OCM) to C2 hydrocarbons (C2H4 and C2H6) has aroused worldwide interest over the past decade due to the rise of vast new shale gas resources. However, obtaining higher C2 selectivity can be very challenging in a typical OCM process in the presence of easily oxidized products such as C2H4 and C2H6. Regarding this, different types of catalysts have been studied to achieve desirable C2 yields. In this review, we briefly presented three typical types of catalysts such as alkali/al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 89 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…Hence, it is very necessary to achieve catalysts with improved performance. 19,20 Besides the most widely studied OCM catalysts such as Li/MgO, 21−24 pure or doped rare earth oxides, 16,25−27 and Mn/Na 2 WO 4 /SiO 2 , 28−31 composite oxides such as ABO 3 perovskites 32−34 and A 2 B 2 O 7 pyrochlores 35,36 also exhibit promising OCM performance, but researchers are still short of a systematic understanding on their structure−reactivity relationship.…”
Section: Ch H M O Ch M Ohmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is very necessary to achieve catalysts with improved performance. 19,20 Besides the most widely studied OCM catalysts such as Li/MgO, 21−24 pure or doped rare earth oxides, 16,25−27 and Mn/Na 2 WO 4 /SiO 2 , 28−31 composite oxides such as ABO 3 perovskites 32−34 and A 2 B 2 O 7 pyrochlores 35,36 also exhibit promising OCM performance, but researchers are still short of a systematic understanding on their structure−reactivity relationship.…”
Section: Ch H M O Ch M Ohmentioning
confidence: 99%
“…Since the early studies in the 1980s, numerous catalyst formulations have been investigated for OCM, but a catalyst that can meet the demands of industrialization has not yet been accomplished. Hence, it is very necessary to achieve catalysts with improved performance. , Besides the most widely studied OCM catalysts such as Li/MgO, pure or doped rare earth oxides, , and Mn/Na 2 WO 4 /SiO 2 , composite oxides such as ABO 3 perovskites and A 2 B 2 O 7 pyrochlores , also exhibit promising OCM performance, but researchers are still short of a systematic understanding on their structure–reactivity relationship.…”
Section: Introductionmentioning
confidence: 99%
“…MnNaW/SiO 2 is one of the most studied and promising catalysts due to its high C2 yield and stability on stream. ,, Serres et al showed that increasing the quantity of active sites in the catalyst contributes to an increase of the catalytic activity up to 19.5% . However, by increasing the concentration of active sites up to 41%, a drop in activity is observed, and associated with a loss of surface area.…”
Section: Oxidative Coupling Of Methane (Ocm)mentioning
confidence: 99%
“…The oxidative coupling of methane has been vastly developed and described in the open literature since the work of Keller and Bhasin . Important review papers reveal the particularities of the OCM reaction in detail. , Specific attention to the OCM process engineering and the reaction mechanism has been paid and will be discussed in this review. More specifically the nature of the catalysts and supports with a significant impact on the reaction will be considered. , In addition, the impact of several parameters such as temperature, space velocity, dilution, and others will be addressed, and preferable conditions favoring the OCM reaction will be revealed.…”
Section: Introduction: From Low-carbon To Zero-carbon Futurementioning
confidence: 99%
“…Ever since OCM was first reported in the early 1980s, more than 2000 catalyst formulations have been discovered for it. [1][2][3] Generally, a favorable catalyst for OCM exhibits good thermal resistance, appropriate surface basicity, 4,5 considerable oxygen ion conductivity, 6 and a substantial amount of oxygen vacancies for generating reactive oxygen anions. 7,8 To industrialize OCM, there is a need to develop catalysts having excellent efficiency, which is a great challenge that relies on achieving a breakthrough in catalyst design.…”
Section: Introductionmentioning
confidence: 99%